On the environmental competitiveness of sodium-ion batteries under a full life cycle perspective – a cell-chemistry specific modelling approach. Issue 24 (12th November 2021) - Peters, Jens F.; Baumann, Manuel; Binder, Joachim R.; Weil, Marcel
Abstract : Assessing different sodium-ion against current lithium-ion battery cells shows large difference between cell chemistries and a good environmental performance for manganese and Prussian blue-based cathodes under a full life cycle perspective. Abstract : Sodium-ion batteries (SIB) are among the most promising type of post-lithium batteries, being promoted for environmental friendliness and the avoidance of scarce or critical raw materials. However, the knowledge-base in this regard is weak, and comparatively little is known about the environmental performance of different SIB types in comparison with current lithium-ion batteries (LIB) under consideration of the whole battery life cycle ('cradle-to-grave'). This work provides a complete and comprehensive update of the state of knowledge in the field of life cycle assessment of SIB. It develops and discloses a specific tool for dimensioning and assessing SIB cells, including a cell-specific model of an advanced hydrometallurgical recycling process. It provides the corresponding inventory data for five different types of SIB and compares their environmental impacts with those of competing LIB, taking into account the full life cycle (cradle-to-grave) and an individual cell dimensioning based on electrochemical considerations. Recycling is found to be highly relevant for minimizing environmental impacts of the batteries, though its benefit depends strongly on the individual cell chemistry. Deep recycling might not be favourable for cathodes based on abundant materials and could even increase impacts. Especially the assessed manganese and nickel–manganese based SIB chemistries show promising results, given that they achieve at least similar lifetimes as their LIB counterparts.